Issue Challenges and Future Prospects of E-Governance in India - Sapna Devi (MultiTech Publisher, 2024)
E-Governance in India has emerged as a vital mechanism for improving the efficiency and transparency of government services. This paper explores the current state of e-governance in India, focusing on the issues, challenges, and future prospects of this digital transformation. The background highlights the growing importance of information and communication technology (ICT) in public administration and the Indian government's initiatives to implement e-governance through programs like Digital India. The digital divide, especially in rural areas, remains a significant barrier, limiting access to online services. Data security and privacy concerns also pose risks to the successful implementation of e-governance systems. Additionally, inadequate infrastructure and limited digital literacy are major challenges that need to be addressed to ensure inclusive and effective e-governance. The paper suggests that overcoming these challenges requires a multi-faceted approach, including improving digital infrastructure, enhancing digital literacy, and ensuring robust data protection measures. The future prospects of e-governance in India are promising, with potential benefits including more efficient public services, increased transparency, and enhanced citizen participation in governance.